Professionalization of the Managerial Capital in the Healthcare Field: a Case of Ukraine - Borshch, Viktoriia (International Journal of Scientific Research and Management (IJSRM), 2020)
Main challenges, priorities and trends of the national health care are analyzed in the paper. The general concept of managerial capital was defined; its main sources were analyzed. Objective processes of developing a professional management system have been viewed. Within the framework of the forming organization’s management capital the following tasks of healthcare facilities’ management were determined. In the paper it is argues, that the process of managerial capital formation is ongoing in the frameworks of managerial staff’s professionalization. Thus, the main directions and variants of professionalization of managerial staff in healthcare field are proposed. But nevertheless, it is important to emphasize, that professionalization of managerial staff in Ukrainian health care is very complicated process, due to the lack of special training basis for its realization and, especially, understanding of government its necessity. The problem of forming and developing managers of healthcare facilities has been emphasized in the paper. Requirements for modern healthcare professionals have been identified.